(untitled) (Progressive Agriculture, 2017)
Sunflower oil contain high concentrations of essential polyunsaturated fat with antioxidant vitamin E. The study was carried out on Swiss Albino healthy mice to evaluate the effects of additional supplementation of sunflower oil in feed on body weight, hematological parameters (total erythrocyte count and hemoglobin concentration) and biochemical parameters (total serum cholesterol, triglycerides, high density lipoproteins, low density lipoprotein and serum creatine). A total of 20, three-weeks old mice were randomly divided into two equal groups ( n=10) as A and B. Group A was considered as control (standard poultry pellet) and group B was supplemented with sunflower oil (5 mL/kg feed) respectively in addition to standard poultry pellet for 50 days. At the end of experimental trial, the mice were sacrificed for analysis of hemato-biochemical parameters. Body weight was significantly (P<0.05) higher in sunflower oil supplemented group compared to control. The total erythrocyte count and hemoglobin concentration were increased significantly (P<0.05) in group B compared to control group A. The total serum cholesterol, HDL and LDL values increased significantly (P<0.05) whereas the triglycerides concentration decreased significantly (P<0.05) in sunflower oil treated group compared to control group. On the other hand serum creatinine value showed non-significant trend to increase (P<0.2). These results suggest that sunflower oil may have beneficial effects to maintain healthy life style. Although further studies are needed to find out the molecular mechanism and its toxicological aspect if any. Progressive Agriculture 28 (1): 36-41, 2017